Analysis of the leakage in a water-lubricated twin-screw air compressor. (5th June 2019) - Wang, Chuang; Xing, Ziwen; Chen, Wenqing; Sun, Shizhong; He, Zhilong
Highlights: Liquid water is modeled in the form of water film and water droplets respectively. A separated flow model is developed to calculate film thickness in rotor tip clearance. The leakage through shaft seals is considered in modeling working process. Leakages through rotor tip clearance and discharge end-face clearance have an important effect on compressor performance. The effect of compression start blow hole, suction end-face clearance and contact line can be neglected. Abstract: For water-lubricated twin-screw compressors, the estimation of leakage flow remains one of the most important problems related to screw compressor design, performance prediction and improvement. In this paper, a mathematical model of working process including detailed leakage and heat exchange models is constructed for this purpose, and the calculated results are verified by measured data. Based on the proposed model, the leakage in the water-lubricated twin-screw air compressor are analyzed. The effects of each leakage path on compressor performance including volumetric efficiency, indicated power and specific indicated power at different rotating speed are calculated and discussed. The prediction of leakage distribution could be used to optimize the compressor design.